PERLINDUNGAN HUKUM TERHADAP PERUSAHAAN PEMBIAYAAN KONSUMEN SEBAGAI PENERIMA FIDUSIA YANG OBJEK JAMINAN FIDUSIANYA TERKAIT SEBAGAI BARANG BUKTI DALAM PERKARA TINDAK PIDANA (STUDI PUTUSAN NO. 04/Pdt.Plw/2015/PN.STB) - DEWI ARTIKA (PREMISE LAW JURNAL, 2017)
ABSTRACT The objective if the research is to find out the status of fiduciary collateral confiscated by the State and legal protection for Consumer Financing company as the creditor of fiduciary holder in order to avoid financial loss. The exhibit is fiduciary collateral of PT. Oscar Kredit Ekspress which is bound in fiduciary collateral contract with Hariani as the fiduciary giver. The status of fiduciary collateral, based on the court’s ruling, has shifted to the ownership from PT. Oscar Kredit Ekspress to the State. In consequence, PT. Oscar Kredit Ekspress suffers financial loss; therefore, it lodges an objection to the Stabat District Court which hands down a Ruling No. 04/Pdt.Plw/2015/Pn.Stb which states that the fiduciary collateral confiscated by the State, becomes the authority of the holder of fiduciary collateral certificate, based on the principle of droit de suite and droit de preference stipulated in Law No. 42/1999 on Fiduciary. Keywords: Consumer Financing, Exhibit, Criminal Act